women's health literacy and some related factors in Mashhad - Maryam Khazaei; Hadi Tehrani; Mohammad Vahedian-Shahroodi; Habibullah Esmaily; Ali Taghipour (Mashhad University of Medical Sciences, 2021)
Background and Objective: Health literacy is the degree to which an individual has the capacity to obtain, process, and understand basic health information and services to make appropriate health decisions. Women's health literacy is an important skill to participate in the prevention and promotion of public health. This study was aimed to investigate women's health literacy and some related factors in Mashhad.   Materials and Methods: This is a descriptive study that was performed on 400 women referring to cultural centers of Mashhad municipality in 2018-2019. A personal information questionnaire and a short form of functional health literacy questionnaire in adults were used to assess the data. Statistic software (SPSS 16) were used to conduct descriptive tests (Frequency, mean, and standard deviation) and analytical statistics (Kruskal-Wallis, Mann-Whitney, and ordinal logistic regression).   Results: The results of this study showed that 16.5% of women participants had inadequate health literacy، 19.8% had border health literacy, and 63.7% had adequate health literacy. Health literacy was significantly related with education, and with the improvement of education level, the score of health literacy also increases. However, no significant relationship between health literacy and age, income, marital status, and employment was observed.   Conclusion: More than one-third of women had inadequate or border health literacy.  Considering the important role of women in family and community health and the impact of health literacy on this important role, it is necessary to design and implement educational programs to promote health literacy skills in them.